North American Prairie Is a Source of Pollen for Managed Honey Bees (Hymenoptera: Apidae). Issue 1 (23rd February 2021) - Zhang, Ge; St. Clair, Ashley L; Dolezal, Adam G; Toth, Amy L; O'Neal, Matthew E
Abstract: Prairie was a dominant habitat within large portions of North America before European settlement. Conversion of prairies to farmland resulted in the loss of a large proportion of native floral resources, contributing to the decline of native pollinator populations. Efforts to reconstruct prairie could provide honey bees ( Apis mellifera ) a source of much-needed forage, especially in regions dominated by crop production. To what extent honey bees, which were introduced to North America by European settlers, use plants native to prairies is unclear. We placed colonies with pollen traps within reconstructed prairies in central Iowa to determine which and how much pollen is collected from prairie plants. Honey bee colonies collected more pollen from nonnative than native plants during June and July. During August and September, honey bee colonies collected more pollen from plants native to prairies. Our results suggest that honey bees' use of native prairie plants may depend upon the seasonality of both native and nonnative plants present in the landscape. This finding may be useful for addressing the nutritional health of honey bees, as colonies in this region frequently suffer from a dearth of forage contributing to colony declines during August and September when crops and weedy plants cease blooming. These results suggest that prairie can be a significant source of forage for honey bees in the later part of the growing season in the Midwestern United States; we discuss this insight in the context of honey bee health and biodiversity conservation.